CYBERSPACE: PERDEBATAN, PROBLEMATIKA, SERTA PENDEKATAN BARU DALAM TATA KELOLA GLOBAL - Rizki Dian Nursita (UNIDA Gontor, 2019)
Globalization and inter-connectivity in international relations are the results of the development of internet technology. Global internet governance involving various elements has contributed to a number of global changes in terms of economy and industry, politics, and the emergence of social movements. This article aims to provide an overview of the global governance of cyberspace, its elements, dilemmas and debates among actors and elements, and problems in cyber global governance. Through some literature research, the researcher found that global governance of cyberspace requires a new approach that can manage the conflicts between elements, bridge the dilemmas, overcome problems in cyberspace, and become an umbrella for all cyberspace elements; including the stakeholders and cyberspace values.